Geochemical Indication of Formation Water Influx to The Volcanic Hosted Hot Springs of Slamet Volcano, Indonesia - Agung Harijoko; Saefudin Juhri; Sachihiro Taguchi; Kotaro Yonezu; Koichiro Watanabe (Geological Agency, 2020)
DOI:10.17014/ijog.7.1.1-14The Slamet Volcano is an active volcano lying above a sedimentary rock substratum with three complexes of geothermal manifestations: Baturaden, Guci, and Paguyangan. In order to understand the characteristic and origin of the geothermal fluid related to the Slamet volcanic system emphasizing the identification of formation water influx represented by sea water signature in the thermal fluid, the water chemistry has been analyzed including stable isotopes of the hot springs, cold springs, shallow groundwater, rainwater, and river water surrounding the Slamet Volcano. The temperature of manifestations is in the range of 42 - 72°C, while the chloride concentration of the geothermal water is ranging from 17 to 754 mg/L. Specifically, the manifestations in Baturaden are distinctively featured by a huge travertine deposit. The values of Cl/B ratio and non-equilibrium state of the reactive elements indicate the existence of two main geothermal fluid flows discharging as hot springs at Baturaden, Paguyangan, and Guci complexes. Guci hot spring complex shows a similar characteristic as fumarole condensate water from the summit of Slamet Volcano which has been diluted by meteoric water. On the other hand, Baturaden hot spring complex appears to be affected not only by fumarole condensate, but also by the contribution of formation water from marine sedimentary rock. Meanwhile, Paguyangan hot spring is more likely as the outflow of a geothermal reservoir which has also been interacting with marine sedimentary rock. Furthermore, the signature of stable isotope of δ18O and δ2Η shows a significant portion of meteoric water contributing in the dilution of thermal waters.